Impact of Institutions and Policy on Economic Growth: Empirical Evidence - Walid Y. Alali (SSRN, 2010)
We reviewed the empirical evidence for the effect of institutions on per capita GDP growth. Although several of the literature suggested institutions are the primary cause of growth; empirical evidence is somewhat inconclusive. On one hand, it partly reflects that technical limitations - especially heterogeneity - have not been adequately addressed in these studies. On the other hand, there seems to be no consensus on which institutions specifically cause growth. We test the effect of four clusters of institutions (Using Rodrik-2005 Taxonomy) on growth using dynamic GMM panel estimation. The taxonomy provides a functional definition of institutions, allowing us to identify exactly the type of institutions that affect growth. Meantime, our methodology has been technically improved without the need to look for “external” tools to address the problem of homogeneity. More importantly, we can estimate the effects of institutional change (short-term effects of institutions) on growth, without assuming institutional stability.
Keywords: 330; Economic Development; Institutions; Institutions Performance; GMM; Panel Data; Economic Growth